Acute Oral Administration of Single‐Walled Carbon Nanotubes Increases Intestinal Permeability and Inflammatory Responses: Association with the Changes in Gut Microbiota in Mice. Issue 13 (1st February 2018) - Chen, Hanqing; Zhao, Ruifang; Wang, Bing; Zheng, Lingna; Ouyang, Hong; Wang, Hailong; Zhou, Xiaoyan; Zhang, Dan; Chai, Zhifang; Zhao, Yuliang; Feng, Weiyue
Abstract: With the increasing production and widespread potential applications of single‐walled carbon nanotubes (SWCNTs), the possible impacts of oral administration of SWCNTs on gastrointestinal tract at currently occupational exposure limits and potential biomedical applications should be concerned. To address the concerns, mice are orally administrated of SWCNTs at doses of 0.05, 0.5, and 2.5 mg kg −1 body weight per day for 7 d. The investigation shows that SWCNT treatment had promoted intestinal injuries at the acute dose of 2.5 mg kg −1 per day, including increase of histological lesion scores, intestinal permeability, and proinflammatory cytokine (IL‐1β, IL‐6, and TNF‐α) secretion. Analysis of gut microbiota composition using 16S rRNA gene sequencing approach reveals that acute oral administration of SWCNTs induces significant shifts of the predominant microbe phyla from Firmicutes to Bacteroidetes and increases abundance of proinflammatory bacteria Alitipes_uncultured_bacterium and Lachnospiraceae bacterium A4 . These notable findings suggest that SWCNT‐induced intestinal injury is linked to SWCNT interaction with intestinal tract and gut bacteria and the consequent triggering of "metabolic inflammation" responses. Furthermore, the study has shown that oral administration of carbon nanomaterials, including SWCNTs, multiwalled CNTs, and graphene oxide, can lead to different inflammatory responses and specific alteration in gut microbiota in mice. Abstract : The acute oral administration of single‐walled carbon nanotubes (SWCNTs) to mice induces increase in gut permeability, intestinal inflammatory responses, and structure of gut microbiota changes in the intestinal tract. Such impact is linked to SWCNTs that disturb intestinal integrity, perform its antibacterial activity, and drive the compositional alteration in gut microbiota, and consequently, trigger the "metabolic inflammation" responses.